Implementasi Ketentuan Menutup Aurat di Universitas Islam Bandung - Nenti Annisa Putri; Ayi Sobarna; Huriah Rachmah (Bandung Conference Series: Islamic Education, 2023)
Abstract. This study explains the provisions for covering genitalia at Bandung Islamic University, where the phenomenon that occurred was found to be non-disciplined faculty students who were not dressed in Islamic dress. Therefore, the Chancellor of the Bandung Islamic University issued regulations for students which contain technical dress as contained in the Chancellor's regulation No: 252/F.04/Rek/VI/2022 concerning the use of Islamic clothing for students on the Bandung Islamic University campus. The purpose of this research are: 1) Knowing the extent to which the implementation of the provisions for covering genitalia at Bandung Islamic University, 2) Knowing about the application of the provisions for covering the genitals of the Islamic University of Bandung, and 3) Knowing what are the supporting and inhibiting factors in implementing the provisions for covering genitalia at Bandung Islamic University. This study uses a qualitative approach with a case study research method, using data collection techniques in the form of observation, interviews, and documentation studies. The results of the study explain that the implementation of the provisions for covering genitalia at Unisba has not run optimally, this is because in the implementation of non-honed Faculty female students have not fully implemented the Chancellor's regulations. The supporting factors in the implementation of the provisions for covering genitalia at Unisba are the Chancellor who agrees to the existence of Islamic dress guidelines and outside media who also support this program. While the inhibiting factors in the implementation of the provisions for covering genitalia at Unisba are: 1) Communication, the Ruhul Islam has not fully communicated and disseminated Islamic dress regulations. 2) Resources, lack of adequate human resources to control in the field regarding the application of the use of Islamic dress. 3) Disposition (executive attitude), namely the constraints of students who are still found not wearing Islamic dress while on campus. Abstrak. Penelitian ini menjelaskan tentang ketentuan menutup aurat di Universitas Islam Bandung, dimana fenomena yang terjadi ditemukan mahasiswi fakultas non-dirasah tidak berbusana Islami. Oleh karena itu, Rektor Universitas Islam Bandung mengeluarkan peraturan bagi mahasiswa yang berisi teknis berpakaian yang dimuat dalam peraturan Rektor No: 252/F.04/Rek/VI/2022 tentang penggunaan busana Islami bagi mahasiswa di lingkungan kampus Universitas Islam Bandung. Tujuan dari penelitian ini yaitu: 1) Mengetahui sejauh mana implementasi ketentuan menutup aurat di Universitas Islam Bandung, 2) Mengetahui mengenai penerapan ketentuan menutup aurat Universitas Islam Bandung, dan 3) Mengetahui apa saja faktor pendukung dan penghambat dalam melaksanakan ketentuan menutup aurat di Universitas Islam Bandung. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian studi kasus, menggunakan teknik pengumpulan data berupa observasi, wawancara, dan studi dokumentasi. Hasil penelitian menjelaskan bahwa implementasi ketentuan menutup aurat di Unisba belum berjalan dengan maksimal, hal ini dikarenakan dalam pelaksanaan di lapangan mahasiswi Fakultas non-dirasah belum sepenuhnya mengimplementasikan peraturan Rektor. Adapun faktor pendukung dalam implementasi ketentuan menutup aurat di Unisba adalah Rektor yang menyetujui adanya pedoman busana Islami dan media pihak luar turut mendukung program ini. Sedangkan faktor penghambat dalam implementasi ketentuan menutup aurat di Unisba yaitu: 1) Komunikasi, pihak Ruhul Islam belum sepenuhnya mengkomunikasikan dan mensosialisasikan terkait peraturan berbusana Islami. 2) Sumber daya, kurangnya sumber daya manusia dalam jumlah yang memadai untuk mengontrol di lapangan terkait penerapan penggunaan busana Islami. 3) Disposisi (Sikap pelaksana), yaitu kendala dari mahasiswa masih ditemukan yang tidak berbusana Islami pada saat berada di lingkungan kampus.